Functional anorectal studies in patients with low anterior resection syndrome. Issue 3 (18th June 2021) - Chen, Ssu‐Chi; Futaba, Kaori; Leung, Wing Wa; Wong, Cherry; Mak, Tony; Ng, Simon; Gregersen, Hans
Abstract: Background: Most patients who have undergone low anterior resection suffer from bowel dysfunction postoperatively. This condition is referred to as low anterior resection syndrome (LARS). The aim was to study defecatory patterns in LARS patients compared to a primary control group of fecal incontinence (FI) patients and normal subjects (NS) with the Fecobionics device. Methods: Fecobionics expulsion parameters were assessed in an interventional study design. The Fecobionics probe contained pressure sensors at the front, rear, and inside the bag. The bag was distended until urge sensation in rectum in 11 LARS patients (5F/6M, 63.2 ± 2.9 years), 11 FI subjects (7F/4M, 64.4 ± 2.5 years), and 11 NS (7F/4M, 63.6 ± 3.0 years). Defecation indices were computed from the Fecobionics data. All subjects had high‐resolution anorectal manometry (ARM) and balloon expulsion test (BET) done. Symptoms were evaluated with LARS and Wexner scores. Key Results: The LARS score in the LARS patients was 39.0 ± 0.6. The Wexner score in the LARS, FI, and NS groups was 14.2 ± 0.7, 10.1±1.0, and 0.0 ± 0.0 ( p  < 0.01). The resting anal pressure and squeeze pressure were lowest in LARS patients ( p  < 0.05). The urge volume was 11.8 ± 4.2, 59.6 ± 6.4, and 41.6 ± 6.4 ml in the LARS, FI, and NS groups, respectively ( p  < 0.001). The expulsion duration did not differ between groups. Defecation indices were lowest in the LARS patients ( p  < 0.05). ARM‐BET confirmed the low urge volume in LARS patients whereas anal pressures did not differ between groups. Conclusions and Inferences: The LARS patients had low anal pressures and urge volume. Most Defecation Indices differed between the LARS group and the other groups. Abstract : Schematic of the Fecobionics system with Fecobionics device and data collection device.